Computational Modeling of the Effect of Sulci during Tumor Growth and Cerebral Edema. (30th May 2016) - Peng, Dan; Zhou, Zhiheng; Liu, Yin; Guo, Tianfu; Li, Ying; Tang, Shan
Abstract : This paper aims at studying the effect of sulci structures during tumor growth and cerebral edema in brain tissues. Motivated by the Intracranial Cerebral Pressure (ICP) monitoring during the brain surgery, a computational model has been created to study macroscopic behaviors of brain tissues with local volume expansion introduced by the tumor growth and cerebral edema. To consider the extra-large deformation during the tumor growth, a nonlinear finite element method has been adopted. Numerical simulation results reveal that sulci structures play significant roles in macroscopic volume expansion and maximum stress of brain tissues. Without considering the sulci structures, predictions on the ICP will be dramatically different from those including sulci structure. Therefore, it is strongly suggested that the sulci structure should be included in future studies on the brain modeling for investigating the space-occupying lesions.